RELIGIOUS MODERATION IN MULTICULTURAL SOCIETIES: UNVEILING THE SOCIO-CULTURAL FOUNDATIONS OF INTERFAITH HARMONY - Hendri Ardianto; I Putu Gelgel; Burmansah Burmansah (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to describe how local factors affect the practice of religious moderation in Pejambon Village, Negeri Katon District, Pesawaran Regency, Lampung Province. The primary focus of this research lies in the role of local leadership in internalizing and implementing the four main pillars of religious moderation, namely national commitment, tolerance, non-violence, and accommodation to local culture in the lives of rural communities. This study uses a qualitative approach with a single case study method. Data collection techniques were done through participatory observation, in-depth interviews, and documentation studies. The research procedure refers to six stages of case studies according to Robert K. Yin, while the informants were selected using purposive sampling and snowball sampling techniques. Data is analyzed through pattern matching, explanation creation, and time series analysis. The study results show that local leadership plays a significant role in contextually building a narrative of moderation through example, deliberation, and social participation. The practice of moderation is not conveyed through formal instruction alone. Still, it is culturally shaped through social interaction, interfaith activities, and strengthening local values that align with national principles. Leadership prioritizing social awareness, openness, and inclusivity has maintained social cohesion and enhanced inter-religious harmony in a pluralistic village. These findings contribute to developing a theory of local leadership based on the values of religious moderation at the grassroots level.